Ellipsometry examination of copper alloys with transitive metals - Filipov, Y.V.; Staschuk, V.S.; Poperenko, L.V.; Vovchenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Electron structure of copper alloys with 3d transition metals (Fe, Co and Cr) have been studied basing on elliposometrical measurement of D and Y in wide spectral range hn = 1.0–4.95 eV. Spectral dependences of Cu-Cr alloys optical conductivity in wide range of chrome concentration (C = 2.5–30 at. %) have been minutely analyzed in this work. Ascertainment that in spectrums of studied alloys (and for copper alloys with other transitive metals) were observed basic band of pure Cu, in addition supplementary band in range 1-2 eV were observed too. Is shown that at small Cr concentrations (C < 5 at. %) alloy is forming a single band similar to copper, with insignificant dependence of Fermi level EF from impurity concentrations. Besides there was founded that in electron structure appear impurity bands situated between Fermi level and d-band of copper. They split on 0.4 eV as a result of spin-orbit interaction. At high impurity concentrations (CCr > 5 at. %) the alloys are heterogeneous mixtures of pure transitive metals and copper based solid solution.